Trace Element Partitioning in ‘Sibera’ Grapevines as Affected by Nitrogen Fertilisation - GÄ…stol, M.; DomagaÅ‚a-ÅšwiÄ…tkiewicz, I. (South African Journal of Enology and Viticulture, 2016)
A study on grapevine cv. Sibera was carried out in a vineyard located near Kraków (Poland) in 2010 and 2011. The plants were treated with three nitrogen application rates (0, 50 and 100 kg N ha-1), administered as ammonium nitrate in a single application three weeks before flowering. Samples of leaf petioles and blades, as well as grapes, were taken. After wet microwave digestion in HNO3, the nutrient elements boron (B), copper (Cu), iron (Fe), zinc (Zn), manganese (Mn), molybdenum (Mo) and sodium (Na), and the trace elements aluminium (Al), barium (Ba), cadmium (Cd), chromium (Cr), lithium (Li), nickel (Ni), lead (Pb), strontium (Sr), titanium (Ti) and vanadium (V), were measured using the ICP-OES technique. Environmental factors such as temperature and available water had a significant effect on the nutrient concentration in the grapes. In the wet and warm 2010 vintage, higher amounts of B, Cu, Cd, Ti and V were measured in the leaves, and of Mn, Al, Ba and Ti in the grape juice. The dry season of 2011 increased the leaf Fe, Mn, Zn, Mo, Na, Ba, Cr, Li and Ni content, which was associated with a higher Zn, Mo, Na, Sr, Cd and Ni concentration in the grape must. The study showed that, in slightly acid soils, mineral N fertilisers containing ammonium can augment the uptake and accumulation of microelements such as Fe, Mn, Zn, Al and Ti by the grape must. In contrast, nitrogen fertilisation depressed the concentrations of some elements, such as B, Fe, Mn, Cd, Cr, Ni and Ti in the leaves. Correlations between the mineral content of the analysed plant tissues are also discussed.